Apprehension-Based Training: A Novel Treatment Concept for Anterior Shoulder Dislocation – A Case Report - Alon Rabin; Livneh Noyman; Noa Yaakobi; Efi Kazum (International Journal of Sports Physical Therapy, 2024)
# Background and Purpose